IMPLEMENTASI SISTEM PENGAWASAN DAN PENGENDALIAN SERTA PENGGUNAAN KOMPUTER PADA LABORATORIUM KOMPUTER SMK ISEN MULANG PALANGKARAYA - Sam'ani, Sam'ani; Qamaruzzaman, Muhammad Haris; Sutami, Sutami (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
Advances in technology and computer surveillance systems at this time have made a significant positive contribution in all fields to support and improve the performance of an order. One of the technological advances in the field of computers is the existence of a system of supervision and control of computer use in a network-based laboratory. At the Isen Mulang Palangkaraya Vocational School, there is still no computer system for monitoring and control of computer use, so students cannot supervise and control computer use during practical activities. Therefore to oversee the use of all computers in the SMK Isen Mulang Palangkaraya laboratory, it is necessary to apply an application system that functions to supervise and control the use of existing computers so that their use is only for practicum subjects not other needs.